(untitled) (Justicia &Derecho, 2026)
This article examines expiration in Peruvian Administrative Sanctioning Proceedings to protect citizens’ rights to legal certainty and predictability in State Contracting Court procedures. Using a qualitative-descriptive methodology, it analyzes the regulatory framework evolution, jurisprudential developments, and interpretive scenarios regarding expiration application in public procurement sanctioning proceedings.